Postoperative Ileus and Postoperative Gastrointestinal Tract Dysfunction: Pathogenic Mechanisms and Novel Treatment Strategies Beyond Colorectal Enhanced Recovery After Surgery Protocols - Mazzotta, Elvio; Villalobos-Hernandez, Egina Criseida; Fiorda-Diaz, Juan; Harzman, Alan; Christofi, Fievos L. (Frontiers in Pharmacology, 2020)
Postoperative ileus (POI) and postoperative gastrointestinal tract dysfunction (POGD) are well-known complications affecting patients undergoing intestinal surgery. GI symptoms include nausea, vomiting, pain, abdominal distention, bloating, and constipation. These iatrogenic disorders are associated with extended hospitalizations, increased morbidity, and health care costs into the billions and current therapeutic strategies are limited. This is a narrative review focused on recent concepts in the pathogenesis of POI and POGD, pipeline drugs or approaches to treatment. Mechanisms, cellular targets and pathways implicated in the pathogenesis include gut surgical manipulation and surgical trauma, neuroinflammation, reactive enteric glia, macrophages, mast cells, monocytes, neutrophils and ICC’s. The precise interactions between immune, inflammatory, neural and glial cells are not well understood. Reactive enteric glial cells are an emerging therapeutic target that is under intense investigation for enteric neuropathies, GI dysmotility and POI. Our review emphasizes current therapeutic strategies, starting with the implementation of colorectal enhanced recovery after surgery protocols to protect against POI and POGD. However, despite colorectal enhanced recovery after surgery, it remains a significant medical problem and burden on the healthcare system. Over 100 pipeline drugs or treatments are listed in Clin.Trials.gov. These include 5HT4R agonists (Prucalopride and TAK 954), vagus nerve stimulation of the ENS—macrophage nAChR cholinergic pathway, acupuncture, herbal medications, peripheral acting opioid antagonists (Alvimopen, Methlnaltexone, Naldemedine), anti-bloating/flatulence drugs (Simethiocone), a ghreline prokinetic agonist (Ulimovelin), drinking coffee, and nicotine chewing gum. A better understanding of the pathogenic mechanisms for short and long-term outcomes is necessary before we can develop better prophylactic and treatment strategies.